Применение информационных технологий и компьютерных средств на уроках химии - Жукова, А.Ю. (My University, 2016)
Relevance of the work lies in the fact that it is difficult for students at chemistry lessons to learn educational material, expounded by the teacher.To understand the material and fixing it in memory, in order to continue applying it for solving both theoretical and practical problems, you need a lot of effort. Using of information and communication technologies will allow the student to get a deeper knowledge on the subject.In this direction, the main objective in teaching is to familiarize students with the basic methods and techniques of chemistry, inculcation of students practical skills using computer programs, corresponding to the content of chemical science. This article discusses the use of information and communication technologies in teaching at chemistry lessons, to improve the effectiveness of students’ work, increasing the number of creative works, expansion of opportunities in further education on the subject.
Keywords: technology of personality-oriented learning; information and communicative technologies; differentiation; multimedia; computer chemical programs